2022
DOI: 10.1002/ldr.4302
|View full text |Cite
|
Sign up to set email alerts
|

Exploring long‐term datasets of land use, economy, and demography variations in karst wetland areas to detect possible microclimate changes

Abstract: This study explores the possibility of deciphering changes in the total area of a karst wetland due to shifts inland use, economy and population over a long-term period (35 years) and microclimate changes . To achieve this goal, we focused on Huangcaozhou Karst Wetland, a national karst wetland park located in China. Based on remote sensing interpretation, long-term climate data, and statistical yearbook datasets, our results showed that from 1984 to 2019, owing to the rapid rates of urbanization and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Comparing these concentrations with the limit values specified for Grade Ⅲ water in the Standard for Surface Water Environmental Quality (GB 3838−2002), Standard Groundwater Quality (GB/T 148−2017), the Standard for Drinking Water Quality (GB 5749−2006), as well as the US EPA drinking water quality standard (Lan et al 2022;EPA, 2006), revealed that concentrations of Al, Pb, Zn, Fe, Cd, Mn, As and Hg in our water samples exceeded all three standard limitations mentioned above. The maximum concentrations of these elements exceeding the standard limitations reached 26.37, 12.40, 1.31, 25.97, 12.20, 20.34, 5.47 and 9.40 times of the standards, respectively.…”
Section: Concentration Changes Of Heavy Metal Elements In the Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing these concentrations with the limit values specified for Grade Ⅲ water in the Standard for Surface Water Environmental Quality (GB 3838−2002), Standard Groundwater Quality (GB/T 148−2017), the Standard for Drinking Water Quality (GB 5749−2006), as well as the US EPA drinking water quality standard (Lan et al 2022;EPA, 2006), revealed that concentrations of Al, Pb, Zn, Fe, Cd, Mn, As and Hg in our water samples exceeded all three standard limitations mentioned above. The maximum concentrations of these elements exceeding the standard limitations reached 26.37, 12.40, 1.31, 25.97, 12.20, 20.34, 5.47 and 9.40 times of the standards, respectively.…”
Section: Concentration Changes Of Heavy Metal Elements In the Watermentioning
confidence: 99%
“…In our integrated health risk study of adults and children exposed to metal elements in water across China, it was observed that health risks in most regions primarily stem from carcinogenic metal elements, particularly Cr in the water (USEPA, 1992;Li, 2020;Lan et al 2022). In our investigation within the Nandong Underground River Basin (NURB), we identified that the main source of health risk for local residents exposed to metal elements in the water is also Cr, followed by Cd and As.…”
Section: Health Risk Assessment Of Heavy Metals In the Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Among these elements, Fe, Al and Mn show the higher concentrations than the other 8 elements, and reach 10 -2 μg•L -1 range. According to the limit values of Grade Ⅲ water specifies in Standard for Surface Water Environmental Quality (GB 3838-2002), Standard for Groundwater Quality (GB/T 148-2017), the Standard for Drinking Water Quality (GB 5749-2006) and the US EPA drinking water quality standard [29,30,31,32,33], the concentrations of Al, Pb, Zn, Fe, Cd, Mn, As and Hg from our water samples exceeded all the three standard limitations mentioned above. Maximum concentrations of all the exceeded standard limitations elements reached 26.37, 12.40, 1.31, 25.97, 12.20, 20.34, 5.47 and 9.40 multiple of standards respectively.…”
Section: Concentration Characteristics Of Heavy Metal Elements In The...mentioning
confidence: 99%
“…Wetlands have the unique characteristics of land and water systems, with distinct ecosystem structures, processes, and functions, e.g., water purification, water conservation, flood storage and regulation, pollution degradation, climate regulation, and regional water cycles [1,2]. Therefore, wetland ecosystems provide important contributions to ecotourism and biodiversity conservation [3][4][5]. Soils are the dominant component of wetlands and play important ecological functions in the wetland biogeochemical cycle and vegetation composition [6].…”
Section: Introductionmentioning
confidence: 99%